Students’ Learning Engagement in the Topic of Atomic Concepts and the Periodic Table - Febriyani, Roseana; Erlina; Mayasari, Eni (Universitas Pendidikan Mandalika, 2025)
Learning engagement constitutes a critical component in the educational process, significantly influencing both the effectiveness of instruction and student academic achievement. This study aims to analyze the learning engagement of undergraduate students enrolled in a Chemistry Education program, specifically concerning their engagement with the subject matter of atomic concepts and the periodic system within the context of a general chemistry course. This research adopts a qualitative descriptive approach. Data were obtained through classroom observations, semi-structured interviews, and document analysis. Observational data were collected from a cohort of 31 students participating in lecture sessions. Based on the initial observational findings, 15 students were purposively selected for in-depth interviews, representing three distinct engagement profiles: highly engaged, moderately engaged, and minimally engaged. The results indicate that students' behavioral, emotional, and cognitive engagement levels vary across categories. Behavioral engagement was predominantly classified as